Connecting the dots on vertical transmission of SARS-CoV-2 using protein-protein interaction network analysis – Potential roles of placental ACE2 and ENDOU - Jing, Hongwu (Placenta, 2021)
We conducted a protein-protein interaction (PPI) network study searching for proteins relevant to pregnancy-associated COVID-19 in pregnancy complicated with severe preeclampsia (sPE) and intra-amniotic infection and/or inflammation (Triple-I). PPI networks from sPE and Triple-I were intersected with the PPI network from coronavirus infection. Common proteins included the SARS-CoV-2 entry receptor ACE2 and ENDOU, a placental endoribonuclease homologous to Nsp15, a protein produced by the virus to escape host immunity. Remarkably, placental ENDOU mRNA expression far exceeded that of ACE2. Immunohistochemistry confirmed ENDOU localization at the hemochorial maternal-fetal interface. Investigation of ENDOU's relevance to vertical transmission of SARS-CoV-2 is further warranted.